High‐Entropy Sulfides as Electrode Materials for Li‐Ion Batteries. Issue 8 (5th January 2022) - Lin, Ling; Wang, Kai; Sarkar, Abhishek; Njel, Christian; Karkera, Guruprakash; Wang, Qingsong; Azmi, Raheleh; Fichtner, Maximilian; Hahn, Horst; Schweidler, Simon; Breitung, Ben
Abstract: High‐entropy sulfides (HESs) containing 5 equiatomic transition metals (M), with different M:S ratios, are prepared by a facile one‐step mechanochemical approach. Two new types of single‐phase HESs with pyrite ( Pa ‐3) and orthorhombic ( Pnma ) structures are obtained and demonstrate a homogeneously mixed solid solution. The straightforward synthesis method can easily tune the desired metal to sulfur ratio for HESs with different stoichiometries, by utilizing the respective metal sulfides, even pure metals, and sulfur as precursor chemicals. The structural details and solid solution nature of HESs are studied by X‐ray diffraction, transmission electron microscopy, energy‐dispersive X‐ray spectroscopy, electron energy loss spectroscopy, X‐ray photoelectron spectroscopy, inductively coupled plasma optical emission spectroscopy, and Mössbauer spectroscopy. Since transition metal sulfides are a very versatile material class, here the application of HESs is presented as electrode materials for reversible electrochemical energy storage, in which the HESs show high specific capacities and excellent rate capabilities in secondary Li‐ion batteries. Abstract : High‐entropy sulfides (HESs) containing 5 equiatomic transition metals, with different M:S ratios, are prepared by a facile one‐step mechanochemical approach. Two new types of single‐phase HESs with pyrite ( Pa ‐3) and orthorhombic ( Pnma ) structures are obtained and structurally characterized in detail. HESs are for the first time applied as electrode materials for battery applications.